Cross cultural perspectives in child advocacy - Berson, Ilene R.; Berson, Michael J.; Cruz, Bárbara C. (Research in global child advocacy., 2001)
This study on cross cultural perspectives in child advocacy deals with various topics, including support for children's issues, the factors that influence reporting of suspected child abuse and child advocacy's application to education professionals. The study looks at issues from around the world.